ABSORPTION COSTING AND ACTIVITY-BASED COSTING METHODS IN MANUFACTURING AND SERVICE SECTORS (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article is about cost management systems which play a crucial role in organizations by providing a structured approach to monitor, control, and optimize costs. These systems are researched to track and analyze expenses across various departments and activities, enabling businesses to make informed decisions and improve their financial performance. From a strategic perspective, cost management systems help organizations identify cost drivers, understand cost behavior, and allocate resources effectively. They also facilitate budgeting and forecasting processes, allowing businesses to set realistic financial targets and monitor their progress. When it comes to the importance of cost management systems, different stakeholders have varying perspectives. From the perspective of top management, these systems provide valuable insights into cost structures and help identify areas of inefficiency or waste. This enables management to take proactive measures to reduce costs, enhance profitability, and gain a competitive edge in the market. For finance departments, cost management systems streamline financial reporting and enable accurate cost allocation, ensuring compliance with accounting standards and regulations.